Effects of the Intermittent Theta Burst Stimulation of the Cerebellar Vermis on Balance Recovery After Stroke: A Study Protocol for a Randomized Controlled Trial - Wang, Lin; Huang, Guilan; Zhang, Li; Yang, Jinyu; Ren, Caili; Liang, Chengpan; Shen, Ying; Su, Bin (Frontiers in Aging Neuroscience, 2022)
Background The recovery of balance function is a critical segment in the rehabilitation treatment of stroke. The cerebellum is considered as the key structure involved in balance and motor control. The cerebellar vermis plays an important role in integrating vision, proprioception, and sensory skin input and may be a candidate stimulation target for regulating the motor network related with balance. However, evidence that the intermittent theta burst stimulation (iTBS) of cerebellar vermis can promote the recovery of balance function after stroke remains insufficient. Therefore, this study aims to explore the efficacy of the cerebellar vermis iTBS for the treatment of balance function in patients with stroke. Methods and Analysis Forty patients with stroke will be recruited in this prospective, randomized, sham-controlled trial. Participants will be randomized in a 1:1 ratio to receive either 15 sessions of cerebellar vermis iTBS (600 pulses) or sham stimulation. Additionally, a routine rehabilitation therapy follows the intervention. The primary outcome is the Berg Balance Scale, and the secondary outcomes are the Fugl–Meyer assessment of the lower extremity and modified Barthel index. The above outcomes will be assessed before intervention and at the end of each week. Pre- and post-iTBS resting-state functional magnetic resonance imaging (rs-fMRI) will be acquired, and the regional homogeneity, fractional amplitude of low-frequency fluctuation and functional connectivity will be calculated and analyzed. Discussion This protocol holds promise as a potential method to improve balance function in patients with stroke. If the outcomes of patients improve after the intervention, the study will provide new insights into improving balance function. Ethics and Dissemination This study has been approved by the Medical Research Ethics Committee of Wuxi Mental Health Center (Wuxi Tongren Rehabilitation Hospital). Results will be disseminated through (open-access) peer-reviewed publications, networks of scientists, professionals, and the public and presented at conferences. Clinical Trial Registration Number www.chictr.org.cn, identifier ChiCTR2100052590.